2012
DOI: 10.1016/j.biomaterials.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of a silicone‒cationic steroid antimicrobial coating to prevent implant-related infection

Abstract: Active release antimicrobial coatings for medical devices have been developed to prevent and treat biofilm implant-related infections. To date, only a handful of coatings have been put into clinical use, with limited success. In this study, a novel antimicrobial compound was incorporated into a silicone (polydimethylsiloxane or PDMS) polymer to develop a novel active release coating that addressed several limitations of current device coatings. The efficacy of this coating was optimized using an in vitro flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 62 publications
6
65
0
Order By: Relevance
“…First, our previously published studies have indicated that the MRSA isolate used in this study produces biofilms on PEEK material [19][20][21][22]. Second, PEEK is commonly used in spinal implant surgeries and these data may provide an indication of MRSA biofilm formation on PEEK materials that may be relevant to other clinical applications.…”
Section: Materials and Machiningmentioning
confidence: 89%
See 4 more Smart Citations
“…First, our previously published studies have indicated that the MRSA isolate used in this study produces biofilms on PEEK material [19][20][21][22]. Second, PEEK is commonly used in spinal implant surgeries and these data may provide an indication of MRSA biofilm formation on PEEK materials that may be relevant to other clinical applications.…”
Section: Materials and Machiningmentioning
confidence: 89%
“…1A). To determine whether the growth of MRSA biofilms would be reduced or prevented on the surface of the two vitamin E-loaded samples (HXL VE 150 kGy and HXL VE 75 kGy) in comparison to the other three clinically relevant material types (HXL, CM, and PEEK), each material type was tested for biofilm formation using a flow cell system developed by the Bone and Joint Research Laboratory at the George E. Wahlen Department of Veterans Affairs (Salt Lake City, UT, USA) [19]. The flow cell consisted of six chambers, each having a dimension of 4 cm 9 4 cm 9 2 cm (Fig.…”
Section: Materials and Machiningmentioning
confidence: 99%
See 3 more Smart Citations